CHI '13 Extended Abstracts on Human Factors in Computing Systems 2013
DOI: 10.1145/2468356.2468564
|View full text |Cite
|
Sign up to set email alerts
|

Comparing avatar game representation preferences across three age groups

Abstract: Avatar representation is an important interaction component of game design. In a game study of 36 mixed-age participants (teenagers, younger adults and older adults), we investigated three distinct types of avatars to differentiate user preferences and interests, primarily to determine if age affected the rating of these modalities. The results identified significant differences in the perceived attractiveness, homophily, engagement and expressiveness of the avatar representations across the three age groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, there is very little research exploring the use of avatars by older adults and how they can provide opportunities for exploring identities. As we have mentioned, studies suggest that older adults create ageless avatars [8,28,31], but it is not clear if this is the purpose of the users or a limitation of the interface which may not be providing choices to make their avatars look more like themselves. Our study aims to understand this issue by exploring representational requirements of older adults designing a humanoid avatar.…”
Section: Older Adults and Avatarsmentioning
confidence: 99%
“…However, there is very little research exploring the use of avatars by older adults and how they can provide opportunities for exploring identities. As we have mentioned, studies suggest that older adults create ageless avatars [8,28,31], but it is not clear if this is the purpose of the users or a limitation of the interface which may not be providing choices to make their avatars look more like themselves. Our study aims to understand this issue by exploring representational requirements of older adults designing a humanoid avatar.…”
Section: Older Adults and Avatarsmentioning
confidence: 99%
“…One possible explanation for these results is that the graphical design of the worm-race does not suit well the game preferences of young and well-educated adults because the participant is forced to train using a worm-like avatar. Previous studies reveal that the avatar preferences observed among young adults are more diverse than in any other age group (Rice et al, 2013) and include non-human avatars. Therefore, no systematic negative effect of a worm avatar should be expected in our sample.…”
Section: Nf Format and Gamificationmentioning
confidence: 99%
“…Earlier research into older adults use of avatars has shown characteristics such as youthfulness to be those most valued by older users (Cheong et al, 2011;Rice et al, 2013).…”
Section: Observations From the Technology Explorers Engagement With Tmentioning
confidence: 99%